Effect of 17 Beta-Estradiol Hormone and Cypermethrin Insecticide on Nile Tilapia - Thanomsit, Chutima; Saowakoon, Samnao; Wattanakornsiri, Amnuay; Nanuam, Jakkaphun; Prasatkaew, Witchuda; Nanthanawat, Phochit (Asian Health, Science and Technology Reports, 2018)
This research aimed to investigate the effect of 17-beta estradiol hormone and cypermethrin onto Nile tilapia in both male and female. After exposure to 17-beta estradiol and cypermethrin, they were assessed for the changes in behaviors, external physiological expressions, internal organ characteristics and protein forms. We found that the fish in the control and 17-beta estradiol induction group swam normally, which contrasted with those fish that exposed to cypermethrin in sub lethal level with and without inducing vitellogenin production. Their swimming was very fast, abnormal and directionless. Additionally, the operculum were always moving and there was lesion around their mouth. The scales were loosened and bleeding as well as the internal organs was decayed. After studying the vitellogenin induction using Western blotting technique, we found the protein band of vitellogenin (210 kDa) in only the female fish induced by 17-beta estradiol (6 mg/kg of body weight) and soaked in 0.25 ppm of cypermethrin. Moreover, their plasma gave a positive result (dark brown) in Dot blot testing. Based on our results, we concluded that cypermethrin and 17-beta estradiol hormone resulted in vitellogenin expression in the female of Nile tilapia. Besides, cypermethrin affected the behaviors, physiological expressions and internal organs. This research is concluded that vitellogenin could be used to assess the exposure of 17-beta estradiol mixed with cypermethrin affecting on endocrine gland functions. It would be beneficial to the investigation of environmental quality and fish population in aquatic environment.